Relationship between Oxidative Stress and Diabetes Mellitus (Global Journal of Medical Research, 2022)
Mellitus Diabetes (DM) is a metabolic disorder manifested by an increase in blood glucose level. Lack of insulin secretion by pancreatic β-cells or insulin resistance are factors that contribute to the development of DM. Insulin resistance is affected by a number of factors including oxidative stress, leading to the formation of type 2 diabetes Mellitus (T2DM) or insulindependent diabetes which is a major and rapidly growing global problem through several cellular processes. The current review is a brief account of the various aspects of oxidative stress and their association with diabetes in various ways in which oxidative stress contributes to the pathophysiology of insulin resistance to diabetes.
Keywords: mellitus diabetes (DM); type 2 diabetes mellitus (T2DM); 1 DM (T1DM); reactive oxygen species (ROS)